Genome-wide identification of the RPD3/HDA1 gene family in foxtail millet (Setaria italica) and analysis of their association with plant height - Liang, Hongkai; Zheng, Zhangfei; Yang, Puyuan; Cui, Xiaokuo; Wang, Liwei; Zhi, Hui; Jia, Guanqing; He, Qiang; Diao, Xianmin (Frontiers in Plant Science, 2026)
The RPD3/HDA1 histone deacetylase family members play crucial roles in plant development, influencing traits such as plant height, stress response and fertility. Although, the RPD3/HDA1 family has been characterized in several plant species, its members and functions in foxtail millet remain largely unknown. In this study, we identified 13 SiRPD3/HDA1 genes in foxtail millet and classified them into four distinct phylogenetic groups. Structural analysis revealed conserved exon-intron patterns and motif compositions within each group, implying functional conservation. Two segmental duplication events were detected. The Ka/Ks ratios (<1) suggested that these gene pairs have undergone strong purifying selection. Expression profiling showed that most SiRPD3/HDA1 genes were expressed during reproductive stages, particularly in shoot apical meristem. Promoter analysis revealed multiple phytohormone-responsive cis-elements. Consistently, qRT-PCR assays confirmed that exogenous GA, ABA, MeJA, and IAA triggered distinct, gene-specific expression responses, together suggesting functional divergence of SiRPD3/HDA1 genes in hormone signaling. Importantly, we performed haplotype-based association analysis across 942 natural accessions, covering the entire SiRPD3/HDA1 gene family. This analysis revealed extensive natural variations and identified five candidate genes (Seita.1G034500, Seita.2G042600, Seita.4G235100, Seita.5G190100, and Seita.5G255900) showing strong association with plant height. Subsequently, subcellular localization analysis showed that Seita.2G042600 and Seita.5G190100 are targeted to the nucleus and plasma membrane, respectively, suggesting their distinct functional roles. This study provides a comprehensive characterization of the RPD3/HDA1 family in foxtail millet, identifies potential regulators associated with plant height, and lays a foundation for future functional studies and molecular breeding efforts.